Mentoring Student for Reducing the Number of Illiterates in Reading, Writing and Arithmetic at Puger Wetan Village in Puger Jember - Indah Wahyuni; Nabilla Khoirunisa; Ifny Nadyla Isfalana; Stevanus Rojer Alvando; Moh Fathullah; Agrerogates Tambunan; Muhammad Daffa Ar Rizky (Perkumpulan Dosen Muslim Indonesia, 2024)
The South Coast of Indonesia, especially in the Puger Village area East Subdistrict Puger Jember Regency still face challenge in increase quality education children. Devotion this aiming for describe effectiveness of mentoring programs student Coast through guidance Study in frame reduce number blind reading, writing and arithmetic for students Puger Wetan. Blind numbers of letters, especially blind reading, writing, arithmetic (reading, writing, arithmetic) for elementary school students, becomes problem serious that hinders progress and potential children in the future. Target tutoring for child blind reading, writing and arithmetic more focused on children child class on that is student grades 3-6 are divided into 2 groups that is child who has Can reading, writing and arithmetic and blind children reading, writing and arithmetic. The method used is PAR (Participatory Action Research), namely with identify ability latest students, giving guidance student in accordance level ability, identify appropriate methods, monitoring and evaluation, and review results. As a result, there are improvement ability as much as 36% of students who previously blind reading, writing and arithmetic, so that number blind reading, writing and arithmetic capable decrease as much as 19%.